Employing constant photocurrent method for the study of defects in silicon thin films - Hitendra K. Malik; Sucheta Juneja; Sushil Kumar (Journal of Theoretical and Applied Physics)
Abstract Different optical characterization techniques have been performed on a series of microcrystalline silicon thin films deposited using very high-frequency-assisted plasma-enhanced chemical vapor deposition process. The constant photocurrent method has been employed to study the defects states in density of states spectra of hydrogenated microcrystalline silicon thin films. The photocurrent measurements demonstrate anisotropy in the optoelectronic properties of the material. We have analyzed the optical absorption coefficient from UV spectroscopy and with the help of constant photocurrent method. The spectra have been analyzed in broad region and are presented for both the cases, i.e., surface and bulk light scatterings. The spectra were interpreted in terms of disorder, resulting defect density, crystalline/amorphous volume fractions and material morphology. The subgap-related parameters such as absorption coefficient, characteristic energy E 0 of tail states and density of subgap defect states together with an estimate of the bandgap of silicon films prepared at various crystalline fractions have also been estimated. The density of localized tail states is found to fall exponentially toward the gap with band tail width of about 110 meV.